Primary intraosseous squamous cell carcinoma arising from ameloblastoma of the mandible: A case report. Issue 5 (September 2015) - Hijioka, Hiroshi; Nishihara, Kazuhide; Suzuki, Hajime; Ishida, Takayuki; Kume, Kenichi; Yoshimura, Takuya; Shima, Kaori; Semba, Ichiro; Nakamura, Norifumi
Abstract: Primary intraosseous squamous cell carcinoma (PIOSCC) is a rare odontogenic malignant tumor, and the origin is considered remnant odontogenic epithelium, odontogenic cyst, and rarely benign odontogenic tumors. We report an extremely rare case of PIOSCC arising from ameloblastoma. A 62-year-old man complained a large hard mass at the sublingual to the submental region. The computed tomography images revealed a large multilocular soft tissue mass extending into the bilateral molar areas with expansion of the mandible and also into the subcutaneous layer at the submental and the submandibular regions. He had received a curettage treatment of unicystic ameloblastoma in the right mandible 23 years ago. Malignant odontogenic tumor was suspected, and sectional mandibulectomy following reconstruction using a titanium plate and pedicle latissimus dorsi flap were performed. Histological examination disclosed a close correlation of intraosseous growth of squamous cell carcinoma and ameloblastoma. PIOSCC arising and dedifferentiated from long term existed ameloblastoma was mostly considered. There has been no recurrence and no metastasis for more than five years after the surgical treatment.